Quadrupole lenses with permanent magnets - Bovda, V.A.; Bovda, A.M.; Guk, I.S.; Lyashchenko, V.N.; Mytsykov, A.O.; Onischenko, L.V. (Problems of Atomic Science and Technology, 2022)
The paper presents an overview of up-to-date design and conception of permanent magnet quadrupole lense. The overview covers two classes of magnetic systems that used in the beam transport facilities of accelerators as quadrupoles with fixed gradient and lenses with the field tuning in the wide range.